Multilingualism and gendered immigrant identity : perspectives from Catalonia - Ali, Farah, 1985- (Multilingual Matters, 2023)
"This book examines the intersectionality of gendered, religious identity among Muslim women in Catalonia, and illustrates how this identity is brokered through language use in a multilingual and diasporic context. It offers a unique lens through which we can further our understanding of the role of language in the acculturation process"-- Provided by publisher.
Keywords: Women immigrants -- Spain -- Catalonia -- Social conditions.; Muslim women -- Spain -- Catalonia -- Social conditions.; Catalan language -- Social aspects.; Group identity -- Spain -- Catalonia.; Intersectionality (Sociology) -- Spain -- Catalonia.; Immigrantes -- Espagne -- Catalogne -- Conditions sociales.; Musulmanes -- Espagne -- Catalogne -- Conditions sociales.; Catalan (Langue) -- Aspect social.; Identité collective -- Espagne -- Catalogne.; Intersectionnalité -- Espagne -- Catalogne.; SOCIAL SCIENCE / Emigration & Immigration; Catalan language -- Social aspects; Group identity; Intersectionality (Sociology); Muslim women -- Social conditions; Women immigrants -- Social conditions; Spain -- Catalonia